MEDICAL STUDENT'S MOTIVATION AND ACADEMIC ACHIEVEMENT INCLUDING STUDENT'S BEHAVIOR IN SELECTING MEDICAL FACULTY - Ewangga, Bayu; Azzahra, Taradipa; Budiman, Mochamad Rizki (SAMPURASUN, 2024)
Background: The university level of education serves as the basis for medical education, which is an academic education. In the selection of education, there are factors that influence, among others, motivation, location of origin, and information media. Motivation is the force that drives someone to do something; motivation is divided into intrinsic and extrinsic motivation. Motivation is one of the internal factors that can affect GPA; besides, motivation can also affect one of them: career decisions and readiness to continue studying in the field of medicine Purpose: This study aims to determine the correlation between motivation and academic achievement and the characteristics of the Faculty of Medicine students. Methods: This study used a cross-sectional approach. The sample collection technique used a total sampling technique; as many as 189 respondents filled out the SMMS-R questionnaire, open-ended questions, and requested GPA data. The data analysis used was the Spearman-Rho correlation test. Results: Based on bivariate analysis with the Spearman-rho Correlation test, there is no significant relationship between entry motivation and academic achievement with a value of p = 0.427 and r = 0.058, the average career plan of students after graduating is to become a specialist doctor as many as 91 (48.1%), the average origin of students comes from West Java Province as many as 150 and the city of Bandung as many as 34, and most of the information media used by students are websites as many as 94 (49.7%). Conclusion: There is no relationship between entry motivation and student academic achievement at the Faculty of Medicine, Pasundan University; the majority of students come from West Java Province with the origin of the city or district, namely the city of Bandung; the information media used by students is the website; and student career plans become specialists.